Gambaran Klinis, Tampilan Ekokardiografi, dan Prediktor dari Kejadian Emboli pada Endokarditis Infektif - Muhammad Barri Fahmi; Teuku Istia Muda Perdan; Pranomo Sigit; Danayu Sanni Darmawan; Harmani Kalim; Eka Harmeiwaty; Amiliana Mardiyani; Ario Soeryo; Siska Suridanda; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2012)
Background. There are many risk factors that are associated with embolic events in patients with Infective Endocarditis (IE) ranging from infecting organism, valve location, vegetation morphology, to age. Nevertheless, echocardiography role in predicting embolic events in patients with Infective Endocarditis remains controversial. Some studies reported an increased risk of embolism in patients with large and mobile vegetations, whereas other studies failed to demonstrate such a relationship.Objectives. The aim of this study is to assess the risk factors that are associated with embolic events and to evaluate the role of transthoracic echocardiography (TTE) in predicting embolic events (EEs) in a small group of patients with definite endocarditis according to the Duke criteria.Methods. Subjects more than 17 years of age, who were enrolled in National Cardiac Center Harapan Kita Infective Endocarditis Registry and who had complete TTE recording were selected for this study. Fourteenpatients with definite Infective Endocarditis according to the Duke Criteria who were hospitalised within 2010 – 2011 were examined with M-mode and  two-dimension echocardiogram. The incidence of embolism was compared with the clinical and echocardiographic characteristics (localization and mobility) of the vegetations.Results. Among 14 patients, 5 (35,7%) had one or more EEs. There were no difference between patients with and without embolism in terms of infecting organism, gender and vegetation mobility. Five out of 9 patients (55%) with mitral valve involvement vegetation had EE. No patients with only aortic and tricuspid valve vegetations had EEs. And all of the patents with EE had mitral valve involvement. Thus, there was a significant higher incidence of embolism was present in patients with mitral valve involvement of vegetation (100%, p = 0,038). Conclusion. Our study shows that the involvement of mitral valve on TTE is predictive of embolism.